The structural and electronic impact on the photophysical and biological properties of a series of CuI and AgI complexes with triphenylphosphine and pyrimidine-type thiones1. (2nd June 2015) - Papanikolaou, Panagiotis A.; Papadopoulos, Anastasios G.; Andreadou, Eleni G.; Hatzidimitriou, Antonios; Cox, Philip J.; Pantazaki, Anastasia A.; Aslanidis, Paraskevas
<x xml:space="preserve">Abstract</x> A controllable S, P-coordination environment resulting in selective structural, emissive and antibacterial properties.